Analysis of the Role of Sharia Insurance in the Indonesian Economy - Apriyanti, Nafisa Nur; Abdurrahman, Kustiawan (Islamic Micro Finance Journal, 2024)
This study aims to analyze sharia insurance in Indonesia's economy. Sharia insurance is an institution tasked with helping each other under Islamic law. This study uses a qualitative method in finding out related to the analysis of the role of Sharia insurance, primary and secondary data sources obtained from literature studies, techniques, and data collection are carried out through research reviews related to the role of Sharia insurance, and data analysis techniques are carried out descriptively. Based on the results of this study, it is explained that the mechanism of Sharia insurance is carried out according to the rules of the Islamic religion, including performing a tabarru contract among fellow insurance participants and helping if one of the participants gets a disaster. The role of Sharia insurance in the Indonesian economy is to find out how extensive the implementation of Sharia insurance funds is for people who have participated as participants in Sharia insurance, such as transferring a risk caused by a disaster as a defense for personal or family members and getting used to separating funds so that they can be managed in the future